Two new species of Campanula L. (Campanulaceae) from SW Turkey - Duman, H. (Edinburgh Journal of Botany, 1999)
Two new species of Campanula L. (Campanulaceae) from SW Anatolia are described and illustrated: Campanula yaltirikii H. Duman (sect. Tracheliopsis) and C. koyuncui H. Duman (sect. Rupestres).
Keywords: Campanula; Campanulaceae; new species; Turkey